Enhanced dual function of Ag nanoparticles decorated one-dimensional polymorphic TiO2 composites for sustainable environmental applications - Yuan-Chang Liang; Chih-Chen Kuo (Journal of Science: Advanced Materials and Devices, 2024)
The hydrothermally synthesized rutile-TiO2 nanorods were spin-coated with anatase-TiO2 film and decorated with Ag nanoparticles via sputtering to construct Ag nanoparticles decorated heterophase TiO2 composites. By extending the sputtering duration to altering the Ag content in the TiO2 composition, we aim to investigate the correlation between the microstructures and the dual function of photoelectrochemical photocatalytic and gas-sensing performances for environmental applications. The Ag nanoparticles on the anatase/rutile-TiO2 composites facilitate photon absorption through surface plasmon resonance. Also, Ag nanoparticles contribute the hot electron to enhance the synergy effect in the anatase-TiO2/rutile-TiO2 to prevent recombination of photoinduced carriers under irradiation, thereby strengthening the photocatalytic characteristics. Furthermore, the gas sensing performance is improved due to the electronic and chemical sensitization effects caused by the Ag nanoparticles on the anatase-TiO2/rutile-TiO2 composite. This study demonstrates that tuning Ag nanoparticle content in the anatase/rutile-TiO2 composites is a promising material design strategy for use in highly efficient photoexcited and gas-sensing devices. The proposed Ag nanoparticles decorated polymorphic TiO2 composite nanorods are suitable for eliminating organic pollutants in water and ethanol pollution monitoring.